Studi Karang Mati Sebagai Pengganti Agregat Kasar Pada Adukan Beton - Hendy Ramadana Putra; Tri Sefrus (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2022)
In this area Kaur is an area located in the southern coastel area of Bengkulu Province,The main problem of this research is that there are many dead corals that are not utilized by the surrounding population. The purpose of this research is the number of dead corals, so that they only become coastel waste. The method used is a laboratory test that is guided by SNI 03-1969-1990. Based on the results of the compressive strength of concrete it is known that the coarse agregate of dead coral used is a mixture of 60%. The study used the composition of 1 cement, 1.6 sand, 2.5 coral in the composition of concrete. The results show that the concrete is 60% more improved than the other concretes.